Using dispute systems design to identify, explain and predict trends in the settlement of international commercial disputes: the UNCITRAL and ICC ADR initiatives. (1st January 2013) - Wolski, Bobette
This paper identifies some recent trends in international commercial dispute resolution including efforts to make transnational litigation more attractive, the sense of crisis said to pervade the arbitration community and the growing interest in the use of mediation as an alternative to, or as a component of, arbitration. It takes a critical look at the efforts of UNCITRAL and the ICC to support the use of mediation. Using the theory and principles of dispute systems design, it seeks to explain why UNCITRAL's model law on International Commercial Conciliation and the ICC's ADR clauses and rules have not had a significant impact and why mediation continues to be underused. The paper examines potential obstacles to increased use of mediation, particularly, the lack of recognition given to agreements to mediate and mediated settlement agreements. It concludes with some observations about the future use of mediation and arbitration in the resolution of international commercial disputes.